Towards the CEFR action-oriented approach : factors influencing its achievement in Thai EFL classrooms - Supunya, Nuntapat (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Common European Framework of Reference (CEFR) has been globally accepted as a framework for language teaching, learning, and assessment. Thailand also adopted the CEFR in 2014 to escalate its English education quality in all levels, placing an emphasis on an action-oriented approach nationwide. Few studies have explored the factors influencing the successful CEFR implementation. As such, the current study, framed in a social constructivist case study methodology, used an in-depth interview with four in-service English teachers from four different regions to investigate the factors contributing to the achievement of the action-oriented approach in a Thai EFL context. The thematic analysis revealed thirteen potential factors that teachers believed affected the implementation of the CEFR, categorised into three different levels – policy, administration, and instruction-oriented. The pedagogical and policy implications were further discussed and generalised to other similar contexts.